Compromiso es una blanco mAvil: A study of organizational commitment in Mexico (Global Journal of Management and Business Research, 2011)
The paper explores the evolution of organizational commitment among workers in a Mexican administrative and production facility for a US-based Fortune 500 MNC Over a period of four years there was a transfer of cultural attributes and commitment attitudes from a parent MNC across national borders to the host subsidiary While the parent MNC had the goal of raising workers organizational commitment worldwide this empirical investigation demonstrated that while worker commitment increased so did the transfer of other parent attributes like worker predisposition to collective bargaining and entitlement attitudes towards more satisfying work better supervision better pay and benefit plans more promotion opportunities and more opportunities for coaction and comradeship among employees